Development of rapid evaluation scale for pericardiectomy of tuberculous constrictive pericarditis by 12-lead electrocardiogram - Yanhong Ren; Yanshu Dong; Xinyue Fan; Hongrui Xu; Shuangyi Yin (Journal of Cardiothoracic Surgery)
Abstract Aim We developed a rapid evaluation scale for pericardiectomy through a 12-lead electrocardiogram (ECG), in order to improve the diagnostic accuracy of pericardiectomy of tuberculous constrictive pericarditis. Method In this study, 262 patients with tuberculous constrictive pericarditis (102 patients) and non-tuberculous constrictive pericarditis (160 patients) were selected by convenience sampling method as participants in Hangzhou Red Corss Hospital from January 2018 to April 2023. The expert validity analysis was carried out by cross-sectional investigation combined with the results of the previous expert questionnaire to establish 12-lead ECG-based the rapid evaluate scale for pericardiectomy of tuberculous constrictive pericarditis. Cronbach’α coefficient and Spearman-Brown coefficient were used for the internal consistency reliability of the scale. Exploratory factor analysis was used for structural validity. Receiver operating characteristic (ROC) was used to analyze the sensitivity and specificity of this scale. Results After preliminary verification, the cronbach’α coefficient and Spearman-Brown coefficient were 0.830 and 0.800, respectively. Three factors with feature roots greater than 1.0 were extracted by principal component analysis and maximum variance orthogonal rotation, and the cumulative contribution rate was 57.77%. Each loading factor ranges from 0.427 to 0.863. The sensitivity of the scale was 96.1%, the specificity was 96.9% and the Yorden Index was 93.0%. Conclusions The 12-lead ECG-based rapid evaluation scale for pericardiectomy of tuberculous constrictive pericarditis has high sensitivity, specificity and accuracy, and has certain scientific research and clinical application value.